CEO Tenure, Capital Intensity, Ukuran Perusahaan, dan Tax Avoidance - Anjelina, Ida Ayu Gardynia; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p18, 2024)
This study examines the effect of CEO tenure, capital intensity, and company size on tax avoidance. The companies observed are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 with a total of 181 companies. The number of samples used in this study was 77 companies with a total of 231 observational data obtainedby non-probability sampling method with purposive sampling technique. Data analysis techniques are carried out using multiple linear regression analysis techniques. The results of the analysis show that the longer the CEO has served in the company, the tax avoidance action will increase. The high value of the company's capital intensity will encourage tax avoidance. Similarly, the size of the company is getting lower, the possibility of tax avoidance is also low.   Keywords: Tax Avoidance; CEO Tenure; Capital Intensity; Company Size